A Randomized, Controlled Trial of a Shared Panel Management Program for Small Practices. (4th February 2016) - Bishop, Tara F.; Ryan, Andrew M.; Chen, Melinda A.; Mendelsohn, Jayme; Gottlieb, Daniel; Shih, Sarah; Desai, Priya; Wolff, Elizabeth A.; Casalino, Lawrence P.
Abstract : Objectives: To determine whether a shared panel management program was effective at improving quality of care for patients with uncontrolled chronic disease. Data Sources: Data were extracted from electronic health records. Study Design: Randomized controlled trial of a panel management program initiated by New York City Department of Health and Mental Hygiene. Patients from 20 practices with an uncontrolled chronic disease and a lapse in care were assigned to the intervention (a phone call requesting that the patient schedule a physician appointment) or usual care. Outcomes were visits to physician practices, body mass index measurement, blood pressure measurement and control, use of antithrombotics, and low‐density lipoprotein measurement and control. Principal Findings: Panel managers were able to successfully speak with 1, 676 patients (14.7 percent of the intervention group). There were no significant differences in outcomes between the intervention and usual care groups. Successfully contacted patients were more likely to have an office visit within 1 year of randomization (45.6 percent [95 percent CI: 22.8, 26.9] vs. 38.1 percent [95 percent CI: 36.8, 39.3]) and more likely to be on antithrombotics (24.4 percent [95 percent CI: 17.7, 31.0]) versus those in the usual care group (17.0 percent [95 percent CI: 13.9, 20.0]) but had no other difference in quality. Conclusions: A shared, low‐intensity panel management program run by a city health department did not improve quality of care for patients with chronic illnesses and lapses in care.